Foliar application of three dithiocarbamates inhibits the absorption and accumulation of Cd in wheat. Issue 12 (24th October 2022) - Gao, Zhixin; Huang, Qingqing; Liu, Yetong; Li, Boyan; Ma, Tiantian; Qin, Xu; Zhao, Lijie; Sun, Yuebing; Xu, Yingming
Abstract : Spraying of DTCs can effectively prevent the absorption and accumulation of Cd in wheat and reduce the Cd level in grains. Zn, Mn and Cd were antagonistic in wheat, and the transport of Cd from soil to root and from husk to grain was inhibited. Abstract : In cadmium (Cd) contaminated farmland soil, antagonism between elements can be used to control the absorption and accumulation of Cd in crops through the external application of zinc (Zn) and manganese (Mn). Dithiocarbamates (DTCs) are highly effective fungicides commonly used in farmlands, and DTCs are rich in Zn and Mn. We selected three representative DTCs (propineb, mancozeb, and zineb) for a field experiment in Henan province, China. The effects of DTC on Cd absorption and accumulation in wheat and the interaction of Zn, Mn, and Cd in wheat after spraying of DTC were studied using different application times at the heading stage. The results showed that after foliar spraying of DTCs according to pesticide application requirements, wheat yield was not affected. The Zn and Mn contents in grains increased, with the highest increases being 19.2% and 12.4%, respectively. Zn and Cd as well as Mn and Cd were antagonistic in wheat, and the transport of Cd from soil to root and from husk to grain was inhibited. The bioconcentration factor (grains/soil) decreased from 1.3 to 0.68 and the translocation factor (grains/husks) decreased from 0.76 to 0.35. The Cd content in grains decreased by 60.4%, 52.8%, and 25.6% with mancozeb, propineb, and zineb applications, respectively, and the Cd reduction effect of spraying DTCs twice was better than that of spraying DTCs once and thrice. The results show that DTCs application could reduce the Cd content in wheat grains and realize the dual effects of crop disease prevention and Cd reduction.